PEMBUATAN JOB MIX FORMULA UNTUK CAMPURAN LATASTON HOT ROLLED SHEET – WEARING COARSE MENGGUNAKAN SUMBER QUARY MATERIAL KABUPATEN TANAH BUMBU PROVINSI KALIMANTAN SELATAN - Hadi Gunawan; Rosehan Anwar (INFO-TEKNIK, 2014)
The release of Amendment 1 Technical Specs Revised Regulations of 2010 which about the use of Fillers in a mixture of cement Lataston Hot Rolled Sheet - Wearing Coarse (HRS - WC) is limited the range of a minimum of 1% of the aggregate weight (maximum upper limit not limited) and the quantity of anti-stripping additive usage in the range of 0.2% - 0.4% by weight of the asphalt. The positive impact is at the time of manufacture Mix Design Formula (DMF) and the Job Mix Formula (JMF) provides the free to use Fillers Cement in unlimited maximum limit and no limit on the quantity of the addition of the use of anti-stripping additive initially 0, 3% to 0.4%, so with the use of Fillers Cement unlimited or above 2% and increase the quantity of use of anti-stripping additive to 0.4% the possibility that the Asphalt Mixture Performance will be better. Negative impact to the user while the specification is the difficulty in determining the percentage of ideal Fillers Cement for the Asphalt Mixture Performance results achieved is the maximum result.This study in the laboratory to determine the results of Asphalt Mixture Performance, by raising the value of anti-stripping additives and uses Source Quary Kabupaten Tanah Bumbu South Kalimantan Province whether the results are in the Technical Specifications.Research results generated is Mixed Performance Value Lataston HRS - WC Marshall Stability value that is equal to 1084.52 kg, the Air Cavity Value In A mixture of 5.30%, 3.70 mm kelelehan, Marshall coefficient 293.11 Kg / mm and Optimum Asphalt Content 6,80%. It can be concluded that the use of filler Cement Additives 2.0% and 0.35% Mixed Performance Lataston HRS - WC also Technical Specifications and Materials Use Quary Tanah Bumbu can be used as a construction material Pavement. Keywords: HRS-WC, Filler Cement, Anti Striping, Mixed Performance